(3ahGFO GdRfLHjds - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3YHO GdHGQi GdbhUi s)
(3ChdgG (B:s
(3jGMGaXkG CSQGQ GdRfLHjd ai GdhQi NUUJ ef Gdehdi Hcd cQjeI aef jTJci GdHQO GdbOje HUdHg hChLGYg ai cd jhe hSGYI s
(3BNQgG (B:s
(3hCda UdGI jedC Gdchf YWQgG hCda SdGe Ke Cda JMjI Ydi GdeUWai GdOGYi Edi GdMb HGdgOi hBdg hGdUMH NjQ GdHQjI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B172 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs